Examining Recovery Trajectories After Sport-Related Concussion With a Multimodal Clinical Assessment Approach. Issue 2 (February 2016) - Henry, Luke C.; Elbin, R.J.; Collins, Michael W.; Marchetti, Gregory; Kontos, Anthony P.
Abstract : BACKGROUND: Previous research estimates that the majority of athletes with sport-related concussion (SRC) will recover between 7 and 10 days after injury. This short temporal window of recovery is based predominately on symptom resolution and cognitive improvement and does not accurately reflect recent advances in the clinical assessment model. OBJECTIVE: To characterize SRC recovery at 1-week postinjury time intervals on symptom, neurocognitive, and vestibular-oculomotor outcomes and to examine sex differences in SRC recovery time. METHODS: A prospective, repeated-measures design was used to examine the temporal resolution of neurocognitive, symptom, and vestibular-oculomotor impairment in 66 subjects (age, 16.5 ± 1.9 years; range, 14-23 years; 64% male) with SRC. RESULTS: Recovery time across all outcomes was between 21 and 28 days after SRC for most athletes. Symptoms demonstrated the greatest improvement in the first 2 weeks, although neurocognitive impairment lingered across various domains up to 28 days after SRC. Vestibular-oculomotor decrements also resolved between 1 and 3 weeks after injury. There were no sex differences in neurocognitive recovery. Male subjects were more likely to be asymptomatic by the fourth week and reported less vestibular-oculomotor impairment than female subjects at weeks 1 and 2. CONCLUSION: When the recommended "comprehensive" approach is used for concussion assessment, recovery time for SRC is approximately 3 to 4 weeks, which is longer than the commonly reported 7 to 14 days. Sports medicine clinicians should use a variety of complementing assessment tools to capture the heterogeneity of SRC. ABBREVIATIONS: BESS, Balance Error Scoring System CI, confidence interval DHI, Dizziness Handicap Inventory ES, effect size ImPACT, Immediate Post-Concussion Assessment and Cognitive Test PCSS, Post-Concussion Symptom Scale SAC, Standard Assessment of Concussion SRC, sport-related concussion